Characterizing Antimicrobial Effects of Radiation and Antibiotic Interactions on Staphylococcus aureus and Escherichia coli Using MALDI-TOF MS - Ali Haider; Renáta Homlok; Csilla Mohácsiné Farkas; Tamás Kocsis (Antibiotics)
Background/Objectives: Antibiotic-resistant bacteria are becoming a major challenge in human and veterinary medicine, as well as in food processing. Methods: In this study, the protein diversity in antibiotic-sensitive and -resistant strains of Staphylococcus aureus and Escherichia coli was investigated by exposing them to varying doses of gamma irradiation, with and without antibiotic presence. Changes in bacterial protein profiles were characterized using MALDI-TOF MS to reveal dose-dependent adaptations and potentiation effects under combined irradiation and antibiotic treatments. Results: The results indicate that MALDI-TOF MS effectively differentiates between sensitive and resistant strains, particularly at lower radiation doses (0, 0.2, and 0.4 kGy), with distinct separation in protein spectra. However, at 0.6 kGy, protein profiles plateaued, suggesting a potential threshold effect in radiation response. In 24-h cultures from irradiated Staphylococcus aureus, significant differences emerged in the resistant strain at 0.6 kGy in the presence of antibiotics, with further generational divergence dependent on initial antibiotic exposure. In the case of the sensitive strain, profiles were notably distinct at the 0.4 and 0.6 kGy doses, revealing dose- and treatment-specific responses. For Escherichia coli, generational differences between resistant and sensitive strains were apparent, though antibiotic effects on protein profiles were limited to the 0.6 kGy dose. Conclusions: The results underscore a potentiation interaction between irradiation and antibiotic exposure, affecting protein diversity and adaptation. Sensitive strains displayed heightened proteomic responses to minor treatment variations, while resistant strains exhibited more stable profiles across conditions. The findings highlight MALDI-TOF MS as a valuable tool in detecting proteomic biomarkers linked to bacterial resistance and stress adaptation.